ADMINISTRATIVE BURDEN PAJAK ATAS GIG ECONOMY PERBANDINGAN WITHHOLDING MECHANISM DAN REAL-TIME REPORTING ANTARA INDONESIA (CORETAX) DAN JERMAN (ELSTER) - Nur Huda Prasetyo Syaiful Hadi; Nur Auliya Rahmatika (Mahkamah : Jurnal Riset Ilmu Hukum, 2026)
The rapid growth of platform-based gig economy poses novel challenges for tax administration, particularly concerning withholding mechanisms and reporting obligations for digitally-active informal workers. This study qualitatively examines the procedural effectiveness of tax withholding and reporting systems between Indonesia implementing the Core Tax Administration System (Coretax) with a pooling withholding approach and Germany through the ELSTER platform employing decentralized real-time reporting. Using comparative procedure study and document analysis within the OECD Tax Administration 3.0 framework, the research evaluates regulatory design, administrative burden, and taxpayer compliance in the gig sector. Findings indicate that Germany's ELSTER system demonstrates superior data accuracy through real-time integration between digital platforms and tax authorities, while Indonesia's Coretax offers simplification potential by reducing taxpayer interaction frequency through pooling. However, Indonesia faces significant challenges in digital infrastructure readiness, tax literacy, and platform compliance. The study concludes that a hybrid model integrating pooling withholding with real-time data-sharing principles represents the optimal direction for digital tax administration in gig economies, especially in developing nations navigating digital transitions.